Facile Preparation of Magnetic Nitrogen‐Doped Carbon Microtubes with Co Nanoparticles for Reduction of 4‐Nitrophenol. Issue 13 (4th April 2023) - Du, Hong; Zheng, Jing; Mao, Yi; Pan, Wen‐tao; Zhang, Yan; Zhu, Lin‐yu; Yin, Xue‐Bo; Zhang, Min
Abstract: Heterogeneous catalysts with controllable interface structures are of great importance to demonstrate the relationship between structure and property. Herein, magnetic Nitrogen‐doped carbon microtubes with Co nanoparticles (Fe3 O4 @C−Co) were prepared, which could be used for the reduction of 4‐nitrophenol(4‐NP). In the process, MoO3 @FeOOH core‐shell structure was fabricated, then ZIF‐67 was decorated on the MoO3 @FeOOH. After adding 2‐methylimidazole, MoO3 microrods were removed. Then the prepared FeOOH@ZIF‐67 microtubes are converted to Fe3 O4 @C−Co hybrid microtubes through pyrolysis. Due to the unique structures, the obtained Fe3 O4 @C−Co composites improved the dispersion of Co nanoparticles (NPs), diminished Co leaching, and promoted catalytic activity. The plentiful nitrogen improved electronic conductivity and brought additional active sites. The resulting Fe3 O4 @C−Co implies outstanding catalytic ability towards the reduction of 4‐NP. The synergistic effect between the hollow microtube and the fine dispersed Co NPs within Fe3 O4 @C−Co offered an excellent catalytic efficiency. More particularly, this achievement opens a new avenue to the targeted design of well‐defined nanocatalysts for practical applications in environmental remediation. Abstract : Herein, magnetic Nitrogen‐doped carbon microtubes with Co nanoparticles (Fe3 O4 @C−Co) were prepared. The obtained Fe3 O4 @C−Co exhibited an excellent catalytic performance due to the synergistic effect between the hollow porous nitrogen‐doped carbon support and the dispersed Co nanoparticles. Furthermore, owing to the magnetism of the magnetic Fe3 O4 NPs and newly‐generated Co NPs, the catalysts could be easily collected and recycled, exhibiting potential application in catalytic and other fields.